Cross-Layer Resource Allocation in Wireless Communications: Techniques and Models from PHY and MAC Layer Interaction - Perez-Neira, Ana I; Realp Campalans, Marc (Elsevier Science & Technology, 2008)
Cross-Layer Resource Allocation in Wireless Communications offers practical techniques and models for the design and optimisation of cross-layer resource allocation - one of the hottest topics in wireless communications.Resource allocation in wireless networks is traditionally approached either through information theory or communications networks.